NEEDS ANALYSIS OF ENGLISH FOR TOURISM MATERIAL IN PROMOTING CONTEXTUAL LEARNING - Ni Putu Dian Utami Dewi; Made Novita Dwi Lestari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Commonly in running an ESP, the teacher/lecturer needs to design a learning model which begins with needs analysis, the learners’ goal/target academic, and the student’s ability to cope with the course (Lisa & Kathrin, 2016). In tourism education, it is important to analyze the students’ need analysis and contextual aspects, regarding to tourism terminologies, conversation, language function, and language expression, those aspects will give meaning to the content. The aims of this study are to investigate the types of students’ target needs toward English for tourism material development and to analyze the types of students’ learning needs toward English for Tourism material development. The approach of the study was quantitative research with a cross-sectional survey design. The sample was 114 Cultural and Religious Tourism Study Program in STAHN Mpu Kuturan Singaraja. The instruments used in data collecting were questionnaires and in-depth interviews. The results found that the students need to increase their speaking ability and confidence in using English. The result of the learning needs indicated which the students want the learning process to be more variation, be more adaptive to situations and circumstances, and should be more pleasant.